Plan de negocio para y comercialización de prendas personalizadas, destinadas al cuidado de pacientes con úlceras de decúbito (úlceras por presión), en la ciudad de Quito - Racines Castillo, Doménica Alejandra (2020)
KOMDU Cía. Ltda., is a family business based in the Metropolitan District of Quito, dedicated to the manufacture and marketing of personalized garments for the care of patients with bedsores or pressure ulcers. The organizational structure according to the business model is distributed according their speciality. In its first two years will have three employees. When studying the market of people between 75 and 100 percent of physical disability, the idea of making 100 percent cotton clothes was born, which would take care of the areas affected by the appearance of bedsores on the skin and would deteriorate the patients well-being and self-esteem. To undertake this business are required 33.000,00 dollars, distributed: 60,60 percent with financing from Ban-Ecuador and the remaining 39,40 percent with own resources. For the delivery of the product to the market, its positioning was considered, creating personalized garments for men and women, who have pressure ulcers, designed with specialized seams that do not generate injuries to the skin, with colors and designs that raise self-esteem, providing safety and comfort to the patient. The marketing strategy is based on focus and differentiation, which consists of offering the market a product with different characteristics from those currently available, allowing the customers to perceive it as unique and be willing to acquire it. The market research determined that 3.630 people have a physical disability, ranging from 75 to 100 percent in Quit; from these 2.723 are interested in acquiring the garments and 1987 are willing to buy. The target market therefore, is the group of patients falling within the above range. For this study has been considered the sale of 8 garments per patient on a bi-monthly basis, and 7 percent of the target market is the pessimistic scenario. The financial evaluation was positive, because the NPV is above 1 and the IRR shows that the profitability obtained in the flow of the project and investors is greater a highly profitability and considering its execution viable.